Konsep Prophetic Pragmatism Willy Jenkins: Membangun Ekologi Spiritual untuk Kehidupan Berkelanjutan Menggereja di Indonesia - Tony Salurante (Sekolah Tinggi Alkitab Jember, 2025)
This article examined the concept of Prophetic Pragmatism by William James Jenkins as a foundation for developing ecological spirituality within the context of the church in Indonesia. The study stemmed from the ecological crisis in Indonesia, including environmental degradation, exploitation of natural resources, and the lack of ecological awareness within Christian communities. Using an interdisciplinary theological approach, the article explored the practical dimensions of Prophetic Pragmatism, which emphasized collective action, reconciliation between humans and creation, and solidarity in responding to environmental crises. The findings showed that this paradigm enabled churches to adopt an adaptive and transformative form of ecological spirituality. Churches were called not only to teach environmental doctrines but also to practice ecological justice through advocacy, liturgical renewal, and collective lifestyle changes. The implementation of this concept in Indonesian churches provided a model of ecological sustainability that was locally relevant and contributed to the global Christian witness regarding environmental responsibility. Artikel ini mengkaji konsep Prophetic Pragmatism dari William James Jenkins sebagai landasan untuk membangun spiritualitas ekologi dalam konteks gereja di Indonesia. Latar belakang kajian ini adalah krisis ekologis yang dihadapi Indonesia, seperti kerusakan lingkungan dan eksploitasi sumber daya alam, serta minimnya kesadaran ekologis dalam komunitas Kristen. Dengan pendekatan teologis interdisipliner, artikel ini mengeksplorasi dimensi praksis Prophetic Pragmatism yang menekankan tindakan kolektif, rekonsiliasi manusia dengan ciptaan, dan solidaritas menghadapi krisis. Temuan menunjukkan bahwa paradigma ini memungkinkan gereja mengadopsi spiritualitas ekologis yang adaptif dan transformatif. Gereja dipanggil tidak hanya mengajarkan doktrin lingkungan, tetapi juga mempraktikkan keadilan ekologis melalui advokasi, liturgi, dan perubahan gaya hidup kolektif. Penerapannya di Indonesia dapat melahirkan model keberlanjutan ekologis yang relevan secara lokal dan berkontribusi pada kesaksian global tentang tanggung jawab iman Kristen terhadap bumi.